Peripheral blood microRNA and VEGFA mRNA changes following electroconvulsive therapy: implications for psychotic depression. (4th October 2017) - Kolshus, E.; Ryan, K. M.; Blackshields, G.; Smyth, P.; Sheils, O.; McLoughlin, D. M.
Abstract : Objective: MicroRNAs are short, non‐coding molecules that regulate gene expression. Here, we investigate the role of microRNAs in depression and electroconvulsive therapy (ECT). Methods: We performed three studies: a deep sequencing discovery‐phase study of miRNA changes in whole blood following ECT ( n = 16), followed by a validation study in a separate cohort of patients pre‐/post‐ECT ( n = 37) and matched healthy controls ( n = 34). Changes in an experimentally validated gene target ( VEGFA ) were then analysed in patients pre‐/post‐ECT ( n = 97) and in matched healthy controls ( n = 53). Results: In the discovery‐phase study, we found no statistically significant differences in miRNA expression from baseline to end of treatment in the group as a whole, but post hoc analysis indicated a difference in patients with psychotic depression ( n = 3). In a follow‐up validation study, patients with psychotic depression ( n = 7) had elevated baseline levels of miR‐126‐3p ( t = 3.015, P = 0.006) and miR‐106a‐5p ( t = 2.598, P = 0.025) compared to healthy controls. Following ECT, these differences disappeared. Baseline VEGFA levels were significantly higher in depressed patients compared to healthy controls ( F (1, 144) = 27.688, P = <0.001). Following ECT, there was a significant change in VEGFA levels in the psychotic group only ( t = 2.915, P = 0.010). Conclusion: Molecular differences (miRNA and VEGFA ) may exist between psychotic and non‐psychotic depression treated with ECT.